Carbon dot-based composites for catalytic applications. Issue 13 (12th June 2020) - Chen, Bin Bin; Liu, Meng Li; Huang, Cheng Zhi
Abstract : We summarize the construction methods and influencing factors of CDs-based composites and discuss their catalytic applications, including photocatalysis, chemical catalysis, peroxidase-like catalysis, Fenton-like catalysis and electrocatalysis. Abstract : Carbon dots (CDs) have been regarded as prospective carbon nanomaterials for catalytic applications due to their advantages such as low toxicity, strong and broad optical absorption, high chemical stability, and rapid electron transfer properties. To further improve their function, CD-based composites or hybrid materials have been developed by integrating CDs into different functional nanomaterials such as inorganic nanostructures, biomaterials, polymers and so on. This review presents and discusses the current development of CD-based composites. After the introduction of the methods for the preparation of CD-based composites, we focus on the description of the factors affecting the synthesis of CD-based composites. Lastly, the advantages of CD-based composites in catalytic applications such as photocatalysis, chemical catalysis, peroxidase-like catalysis, Fenton-like catalysis and electrocatalysis are described.